“Correspondencia de los cuidados paliativos a la taxonomía NANDA-I según dimensiones de calidad de vida afectadas en el adulto hipertenso”. - Guevara Mayorga, Johanna Elizabeth (2019)
The palliative citizens form a welfare model aimed at improving the quality of life of the patient and his family. A descriptive investigation was developed; Transversal, mixed, with the aim of associating this form of nursing care, aimed at the care of the hypertensive adult according to the dimensions of quality of life affected in those patients. The selection of the sample followed a non-probabilistic sample called subject-types, consisting of 66 nursing professionals, who elaborate in the health district in the Chambo-Riobamba. As an instrument for data collection, the questionnaire was used, which allowed to explore the professional and social characteristics of research interest, the fulfillment of the actions directed to this type of care. Nursing staff of the female sex with ages under 25 years and professional experience of up to three years predominated; which identified a nurse / patient relationship based on terms of respect, self-confidence, self-control, empathy and acceptance, which needs to be strengthened through training actions. The correspondence was established between the palliative care for the hypertensive adult proposed by Cali-Cobos and the NANDA-I, NOC and NIC taxonomy.